U.S. adults' reasons for changing their degree of willingness to vaccinate against COVID-19. - Koskan, Alexis M.; Teeter, Benjamin S.; Daniel, Casey L.; LoCoco, Iris E.; Jensen, Ulrich T.; Ayers, Stephanie L. (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Introduction: COVID-19 vaccines significantly reduce the risk of complications and hospitalizations due to this virus. When COVID-19 vaccines first became commercially available, roughly 30% of U.S. adults reported being hesitant to receive these newly developed vaccines, and 15% said they would not receive the vaccine. However, by May 2021, 19% of adults were vaccine-hesitant, and 13% refused to vaccinate against COVID-19. It is critical to understand why adults' degree of willingness to vaccinate against COVID-19 changed over time to plan for future pandemics and vaccination campaigns. Methods: We conducted two waves of survey research over five months (January and May 2021) with a panel of 890 U.S. adults. One survey question assessed willingness to vaccinate against COVID-19. The response option included a slider scale ranging from 0 (signifying complete unwillingness) to 10 (complete willingness). We asked participants whose willingness score changed by more than one point to report their rationale for their change in perceptions. We conducted a conventional content analysis on all qualitative responses. Results: We analyzed qualitative responses for 289 participants, 54.7% of whom had not been vaccinated against COVID-19 by May 2021. Among those who remained unvaccinated, 36.1% reported increased willingness to vaccinate. The most commonly cited reasons for becoming more willing to receive the vaccine include believing that COVID-19 vaccines are safe and effective, protecting against the pandemic, and desiring to return to pre-pandemic life. Reasons for increased COVID-19 vaccine hesitancy include vaccine safety concerns, the low perceived need for the vaccine, distrust in how COVID-19 vaccines are made and of larger institutions such as the government and pharmaceutical companies, and concerns about vaccine effectiveness. Conclusion: Findings illuminate the rationale behind individuals' changes in their degree of willingness to vaccinate against COVID-19. It is critical to incorporate these considerations in future vaccine rollout initiatives to increase the public's vaccine confidence.